Is middle East pain syndrome (MEPS) a variant of fibromyalgia syndrome or a distinct disease? - Mona H. Elhamamy; Adel A. Elbeialy; Maha S. Mohamed; Sabah E. Abdelraheem; Hala M. Elzomor (BMC Rheumatology)
Abstract Background Fibromyalgia Syndrome (FMS) is a chronic disabling musculoskeletal condition of unknown aetiology characterized by generalized musculoskeletal pain, extreme fatigue, mood disturbance, impaired cognition, and lack of refreshing sleep. Middle East pain syndrome (MEPS) is a newly described pollution-induced syndrome of hyperparathyroidism and fibromyalgia mimicking rheumatoid arthritis, characterized by the radiological presence of spur-like excrescences in terminal phalanges. This study aimed to explore the inflammatory nature of Middle East pain and Fibromyalgia syndromes. Methods Eighty primary fibromyalgia patients were included in this study. They were divided into two groups, group [1] 1 of 40 FMS patients with low vitamin D levels and secondary hyperparathyroidism, which were diagnosed as MEPS, and group [2] of 40 primary FMS patients. They were subjected to full medical history taking, clinical examination and laboratory assessment including serum IL-17 by enzyme-linked immunosorbent assay technique, as well as assessment of Madrid Sonographic Enthesitis Index (MASEI) using musculoskeletal ultrasound and nailfold capillaroscopic pattern assessment. Plain X-ray films for hands were done on all patients. Results There was a statistically significant elevation of serum IL17 in the MEPS group (median = 58.3 ng/L) compared to the FMS group (median = 45.7 ng/L) as the p-value is < 0.05. Capillaroscopic examination revealed a statistically significant difference between MEPS and FMS groups regarding angiogenesis as the p-value is < 0.05. The ultrasonographic examination also showed a statistically significant difference between MEPS and FMS groups as regards MASEI score as the p-value is < 0.05. Hands X-rays evidenced the exclusive existence of tuft spur-like excrescences in MEPS patients only. Conclusion Elevated IL-17 levels, non-scleroderma pattern capillaroscopic and enthesopathy findings in both MEPS and FMS patients are strongly supportive that inflammatory mechanisms participate in the pathogenesis of both diseases. The significant increase of these findings in MEPS than FMS patients as well as the presence of hand tufts spur-like excrescences, confirm that the newly discovered MEPS is a different disease although it involves fibromyalgia symptoms and signs.